Application of system approach to formation of ecological and humanistic values in the course of school chemical education. (Journal of Educational Sciences, 2016)
The scientific-theoretical principles of system approach to a problem of formation of ecological and humanistic values of school students in the course of school chemical education are considered. Theoretical research of approaches to concept definition «system», consideration of its main signs and properties, selection criteria of its components, allowedus to mark out the main system properties which gave the chance most substantially and to describe precisely formation of ecological and humanistic values of school students in the course of chemistry studying as system, and also its creations already as pedagogical system will be based. For research of system of formation of ecological and humanisticvalues in the course of school chemical education as the most expedient the following aspects of system approach were chosen us: system and component, system and structural, systemic-functional, system and communicative (system and information), system and integration (system and administrative), system and historical (system and genetic). Theconcept of formation of ecological and humanistic values in the course of school chemical education which consists of five theoretical provisions combining all previous and predetermining subsequent the theoretical and methodological material of our research is created.